Nurina Rahmawati PENGARUH PEMBERIAN FITOBIOTIK DALAM PAKAN TERHADAP PERFORMA PRODUKSI AYAM RAS PETELUR UMUR 28 – 32 MINGGU - Nurina Rahmawati (Jurnal Ilmiah Fillia Cendekia, 2020)
ABSTRACT The aim of this reseach was to know the influence of phytobiotic in feed for laying hen production performance at 28 – 32 weeks old . Variables in the study include: water feed consumption, hen day production, feed conversion rasio, feed eficiency and IOFC. The research method used was experimental using Random Design Randomized Design (RAL).The results showed that The treatment P1, P2 and P3 was very significant effect ratio (P<0,01) on feed consumption, hen day production, feed conversion rasio, feed eficiency and IOFC. The highest feed consumption was P2 (phytobiotic 2%) 111,23 g/tail/day; the highest hen day production was P2 (phytobiotic 2%) 83,21 ± 1,36%; the highest feed conversion rasio was P1 (phytobiotic 1%) 2,10 ± 0,04; the highest feed eficiency was P1 (phytobiotic 1%) 2,10 ± 0,04 and the highest IOFC was 12.481,8 ± 204,08 (IDR/tail/28 day). The conclusion of this research, that the influence of phytobiotic 2% is the best result to be increase for feed consumption, hen day production and IOFC laying hen.